A folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme and preparation method thereof

By modifying folic acid and platinum ions on nanosilver particles, silver-platinum bimetallic quantum dot-based nanoenzymes were prepared, which solved the problem of difficulty in detecting mercury and iodine at the same time in the prior art, and achieved high sensitivity and selectivity visibility detection.

CN115656157BActive Publication Date: 2025-03-21QUFU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211086503.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2025-03-21
Estimated Expiration
2042-09-06

AI Technical Summary

Technical Problem

The prior art is difficult to detect mercury (Hg2+) and iodine (I-) simultaneously quickly, easily and at low cost, which is of great significance to environmental protection and human health.

Method used

Through a simple "one-pot synthesis method", folic acid and silver ammonia ions are fully mixed and reduced, chloroplatinic acid is added to modify platinum on the surface of nanosilver particles, and folic acid is prepared to prepare folic acid-stable silver-platinum bimetallic quantum dot-based nanoscope (FA@Ag-Pt QDs). This nanoenzyme adsorbs and modifys precious metal ions through electrostatic action to form a core-shell structure, improving the sensitivity of catalytic activity and visibility detection.

Benefits of technology

It realizes fast, simple and low-cost visibility detection of Hg2+ and I-, with high sensitivity and selectivity, and is suitable for testing in the environmental water, food and medicine fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115656157B_ABST
    Figure CN115656157B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of nanomaterials, and specifically discloses a folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme FA@Ag‑Pt QDs, wherein the bimetallic core-shell quantum dot mimetic enzyme has the advantages of high catalytic efficiency, good stability, monodispersity and rapid separation, and exhibits good simulated peroxidase catalytic activity. The FA@Ag‑Pt QDs material is first reduced by fully mixing folic acid with silver ammonium ions through a simple "one-pot synthesis method", so that the two are controllably modified together through non-covalent self-assembly or coordination bonds, and then chloroplatinic acid is added to modify platinum on the surface of nanosilver particles to obtain the method, which is simple in steps, easy to operate, mild in reaction conditions, and suitable for large-scale production. The FA@Ag‑Pt QDs mimetic enzyme prepared by the present invention has good simulated peroxidase catalytic activity, and has great application value in the fields of environmental water, food, and medicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanomaterials, and in particular relates to a folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme and a preparation method and application thereof. Background Art

[0002] Mercury is a highly toxic heavy metal element. Once it enters the human body, it cannot be excreted. After continuous accumulation, it will cause severe damage to the human body and may affect various parts of the body, such as the nervous, cardiovascular, kidney, gastrointestinal, reproductive, endocrine, respiratory and immune systems. The World Health Organization stipulates that Hg in drinking water is 2+ The content does not exceed 3.0×10 -8 Iodine is an essential trace element for the human body and plays an important role in many physiological processes, such as intellectual development, basic metabolism and neural activity. Low or high levels of iodine can induce a variety of diseases such as hypothyroidism, thyrotoxicosis, thyroid cancer, hyperthyroidism, thyroiditis, cretinism and endemic goiter. The World Health Organization recommends that adults and pregnant women take iodine daily. - The doses are 150 and 250 mg respectively. 2+ and I - The methods include fluorescence spectroscopy, electrochemistry, colorimetry, high performance chromatography, aggregation induced luminescence, etc., and satisfactory results have been achieved. However, most of these methods have expensive instruments and complicated operations. Therefore, it is necessary to build a fast, simple, low-cost, and reliable sensor, especially one that can be used for simultaneous visual detection of Hg 2+ and I - , which is of great significance to protecting the environment and maintaining human health. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention aims to provide a method for simultaneously detecting Hg 2+ and I - Preparation method and application of silver-platinum bimetallic quantum dot-based nanozymes stabilized by biomolecule folic acid. Through a simple "one-pot synthesis method", folic acid and silver ammonium ions are fully mixed and reduced, and then chloroplatinic acid is added to modify platinum on the surface of nanosilver particles to prepare nanosilver platinum core-shell material FA@Ag-Pt QDs. The material can improve the catalytic activity of peroxidase mimics and Hg 2+ and I - The visibility and sensitivity of catalytic colorimetry further expand the practical application of the catalytic performance of nano-mimetic enzymes and the amplification of enzyme-catalyzed colorimetric signals.

[0004] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0005] In a first aspect, the present invention provides a folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme (FA@Ag-PtQDs), in which the Ag and Pt cations are adsorbed onto the surface of folic acid through the electrostatic interaction between the metal Ag and Pt cations and the negative charges or lone pairs of electrons on folate, and then subjected to a reduction reaction to obtain folic acid-stabilized silver-platinum nano-quantum dot particles, wherein the size of the material is at the nanometer level.

[0006] Furthermore, the Ag(NH4)2 + The strong electrostatic interaction between the empty d orbital of Ag and the lone electron pair of N or O makes Ag(NH4)2 + It adheres to the surface of FA salt and is then reduced by a reducing agent to form silver nanomaterials.

[0007] Furthermore, the platinum ions in chloroplatinic acid are adsorbed on the surface of silver nanoparticles through electrostatic action, and the platinum is reduced on its surface by a reducing agent. The two metals coexist, and Pt presents different valence states, which increases the activity and stability of FA@Ag-Pt QDs nanozyme.

[0008] Furthermore, in the FA@Ag-Pt QDs nanozyme, the molar ratio of Ag element to Pt element is 9:1 to 5:5.

[0009] In a second aspect, the present invention provides a method for preparing a folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme, comprising the following steps:

[0010] (1) mixing ammonium folic acid salt, silver ammonium ions and a polyhydroxy alcohol compound to obtain a precursor mixture, stirring the precursor mixture to react; and then adding a reducing agent to reduce the mixture to obtain silver nanoparticles;

[0011] (2) then adding HCl to the reaction mixture to adjust the pH, stirring, adding chloroplatinic acid hexahydrate, adding a reducing agent for reduction, and adding HCl again to adjust the pH;

[0012] (3) The reaction solution was washed by centrifugation with acetone and purified water and dried under vacuum to finally obtain the desired folic acid-stabilized silver-platinum bimetallic nano-quantum dot nanozyme FA@Ag-Pt QDs.

[0013] Furthermore, in the FA@Ag-Pt QDs nanozyme described in step (3), the molar ratio of Ag element to Pt element is 9:1 to 5:5; and the ratio of folic acid to the sum of the molar numbers of Ag and Pt is 0.1:1 to 10:1.

[0014] Furthermore, in step (1), the feed ratio of the ammonium folic acid salt to the silver ammonium ion, the polyhydroxy alcohol compound and the reducing agent is 4.42-44.2 mg: 1.54-0.86 mg: 12-20 mL: 0.32-0.44 mg.

[0015] Furthermore, in step (1), the polyhydroxy alcohol compound is at least one of ethylene glycol, glycerol, and polyvinyl alcohol; the polyhydroxy alcohol can control the size of the formed mimetic enzyme and play a dual role as a solvent and a stabilizer.

[0016] Furthermore, in step (1), the folic acid ammonium salt and silver ammonium ions are obtained by completely dissolving folic acid and AgNO3 in a 0.5-3% ammonia solution.

[0017] Furthermore, the pH of the 1% ammonia solution is 8.0-9.0, preferably 8.5.

[0018] Furthermore, in steps (1) and (2), the reducing agent is at least one of vitamin C, hydrazine hydrate, glucose, sodium borohydride, etc.

[0019] Furthermore, the feed ratio of the chloroplatinic acid hexahydrate and the reducing agent described in step (2) to the folic acid ammonium salt described in step (1) is 0.17-0.86 mg: 0.32-0.44 mg: 4.42-44.2 mg.

[0020] Furthermore, the pH value described in step (2) is 5.0-8.0; the preferred pH value is 7.0.

[0021] The third aspect of the present invention provides the application of the FA@Ag-Pt QDs nanozyme in the fields of environmental water, food, medicine, etc.

[0022] Furthermore, the application is to use the FA@Ag-Pt QDs nanozyme to carry out Hg 2+ or I-test, including the following steps:

[0023] S1. Add the colorimetric substrate 3,3',5,5'-tetramethylbenzidine (TMB), disodium hydrogen phosphate-citric acid buffer solution, and the sample solution to be tested to the FA@Ag-Pt QDs standard solution to obtain a test solution;

[0024] S2. Observe the color change of the test liquid.

[0025] Furthermore, in step S1, the standard solution is a FA@Ag-Pt QDs solution with a concentration of 0.005-0.05 mg / mL, preferably 0.02 mg / mL.

[0026] Furthermore, in step S1, the added amounts of the colorimetric substrate 3,3',5,5'-tetramethylbenzidine (TMB), hydrogen peroxide (H2O2), and disodium hydrogen phosphate-citric acid buffer solution are: 200 μL 1.5 mM TMB, 300 μL 1.0 M H2O2, and 200 μL pH 4.0 disodium hydrogen phosphate-citric acid buffer solution.

[0027] Furthermore, in step S2, when the added sample solution causes the color of the sample solution to change from blue to colorless, and the absorption peak of the ultraviolet spectrum at 652nm continues to decrease, it means that the sample solution contains Hg 2+ .

[0028] Furthermore, in step S2, when the added test sample liquid causes the color of the test liquid to change from light blue to blue through a visible color enhancement effect, and at the same time, the absorption peak of the ultraviolet spectrum at 652 nm continues to increase, it indicates that the test sample liquid contains I–.

[0029] FA@Ag-Pt QDs-TMB-H2O2 nanozyme system of the present invention detects Hg 2+ or I – The principle is: using Hg 2+ The reducibility of I can reduce the blue TMB oxide oxidized by FA@Ag-Pt QDs to colorless TMB. – The light blue TMB oxide can be further oxidized to obtain more blue oxTMB. With the excellent catalytic activity of FA@Ag-Pt QDs, the colorimetric Hg 2+ and I-, to achieve the effect of improving the catalytic performance of the nano-mimetic enzyme and amplifying the enzyme-catalyzed colorimetric signal.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] First, the present invention provides a folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme FA@Ag-Pt QDs, which is based on the multiple hydroxyl and carboxyl groups contained in folic acid and the rich nitrogen elements with abundant active sites, the high specific surface area and abundant loaded active sites and anti-pollution performance of platinum nanoparticles, the good catalytic performance shared by silver-platinum nanoparticles, and the superior synergistic enhancement effect between folic acid and precious metals. The core-shell simulated enzyme material has the advantages of high catalytic efficiency, good stability, monodispersity and rapid separation, and exhibits good simulated peroxidase catalytic activity.

[0032] Secondly, the present invention provides a method for preparing FA@Ag-Pt QDs, a silver-platinum bimetallic quantum dot-based nanozyme stabilized by folic acid. The method uses a simple "one-pot synthesis method" to fully mix folic acid and silver ammonium ions and then reduce them, so that the two are controlled to be modified together through non-covalent self-assembly or coordination bonds, and then chloroplatinic acid is added to modify platinum on the surface of nanosilver particles to obtain the target product. The method has simple steps, convenient operation, mild reaction conditions, and is suitable for large-scale production.

[0033] In addition, the present invention provides the application of the FA@Ag-Pt QDs nanozyme in the fields of environmental water, food, medicine, etc. The FA@Ag-Pt QDs mimetic enzyme prepared by the present invention has good mimetic peroxidase catalytic activity; especially in ultra-trace Hg 2+ In the presence of or I–, it can rapidly catalyze the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) under H2O2 conditions, resulting in a visual color change from blue to colorless or from light blue to blue. In addition, common inorganic and organic interferences have a significant impact on the catalytic colorimetric Hg 2+ and I – There is no obvious effect, which shows that the FA@Ag-Pt QDs enzyme mimic synthesized in the present invention has good selectivity and anti-interference, showing the effect of Hg 2+ and I – Very good specificity and selectivity, convenient for efficient detection of trace Hg in environmental water, common beverages, food and pharmaceutical samples 2+ The detection limits of the above two ions are as low as 4.00×10 -10 mol / L and 6.56×10 -8 mol / L, the detection method has the advantages of simple operation, good selectivity, high sensitivity and strong visibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 .UV spectrum test results of FA@Ag-Pt QDs nanomimetic enzymes prepared under different conditions at 652nm: a is the different molar ratios of Ag and Pt, and b is the ratio of the sum of the molar numbers of folate and silver-platinum bimetallic.

[0035] Figure 2 .Structural characterization of the FA@Ag-Pt QDs nano-mimetic enzyme prepared in Example 1, wherein: a is a TEM image (inset: particle size distribution image); b is a DLS image; c is an EDS image (inset: HR-TEM image); d is a fluorescence spectrum image.

[0036] Figure 3.Structural characterization of the FA@Ag-Pt QDs nano-mimetic enzyme prepared in Example 1, wherein: a is the XRD pattern; b is the FT-IR pattern; c is the ζ potential pattern; d is the X-ray photoelectron wide-angle spectrum; e is the XPS high-resolution spectrum of Ag 3d, and f is the Pt 4f spectrum.

[0037] Figure 4 . The effects of different experimental conditions on the catalytic oxidation of TMB in the presence of H2O2 of FA@Ag-Pt QDs prepared in Example 1, where: a is temperature; b is reaction time; c is pH value; d is TMB content and e is H2O2 content. The effects of temperature, reaction time, pH, TMB and H2O2 content on the catalytic oxidation of TMB in the presence of H2O2 of FA@Ag-Pt QDs prepared in Example 1, respectively correspond to Figure 3 ae.

[0038] Figure 5 .Ultraviolet spectroscopy test results of the synergistic enhancement of the peroxidase mimetic activity between the components of FA@Ag-Pt QDs prepared in Example 1, wherein a is the UV-visible absorption spectra of FA, AgPt and FA@Ag-Pt QDs in the presence or absence of H2O2 and the corresponding color changes; b is the time response curve at 652nm corresponding to the curve in Figure a; UV-visible absorption spectrum of the FA@Ag-Pt QDs-TMB-H2O2 system, c is under the conditions of isopropanol and chlorohydroxylammonium, and d is under air saturated and N2 saturated conditions.

[0039] Figure 6 . Steady-state kinetics experiment of FA@Ag-Pt QDs prepared in Example 1, where a is vc TMB and b is vc H2O2 is the steady-state kinetic curve of FA@Ag-Pt QDs, c is 1 / c TMB and d is 1 / c H2O2 , are the double reciprocal curves corresponding to a and b respectively.

[0040] Figure 7 .a shows the effect of common metal ion interferences on the catalytic colorimetric Hg 2+ The inset shows the corresponding color change; b and c are the effects of common anionic interferences and organic interferences on the catalytic colorimetric analysis of the FA@Ag-Pt QDs-TMB-H2O2 system. - The inset shows the corresponding color change; d, e, and f are the common metal ions and Hg 2+ When coexisting, common anions and I - When coexisting, common organic matter and I -The effect of coexistence on the absorption intensity of FA@Ag-Pt QDs-TMB-H2O2 system at 652nm.

[0041] Figure 8 .a is catalytic colorimetric Hg 2+ UV-vis spectroscopic titration curve and its corresponding color change (c Hg 2+ :0,1.00,5.00,16.67,43.33,73.33,116.67,333.33,533.33,833.33,1166.67,1500.00,1666.67×10 -9 mol / L); b is ΔA 652 With c Hg 2+ The linear relationship curve of catalytic colorimetric I - UV-vis spectroscopic titration curve and its corresponding color change (c I - :0,1.00,2.33,3.33,5.00,6.67,10.00,13.33,23.33,43.33,66.67,90.00,100.00×10 -7 mol / L); d is ΔA 652 With cI - The linear relationship curve. DETAILED DESCRIPTION

[0042] The present application will be further described in detail below by way of example so that those skilled in the art can practice the present application. It should be understood that other embodiments may be adopted, and appropriate changes may be made without departing from the spirit or scope of the present application. In order to avoid unnecessary details for enabling those skilled in the art to practice the present application, the description may omit certain information known to those skilled in the art. Therefore, the following detailed description should not be understood in a restrictive sense, and the scope of the present invention is defined only by the appended claims. The following examples are convenient for a better understanding of the present application, but are not intended to limit the scope of the present application.

[0043] Example 1

[0044] (1) 22.1 mg (0.05 mmol) of folic acid and 1.2 mg (0.007 mmol) of AgNO3 were completely dissolved in 5 mL of 1% ammonia solution at pH 8.5; 16 mL of ethylene glycol solvent was added, and the three were stirred and reacted at room temperature for 3 h to obtain a precursor mixture; 1.5 mL (6.7 mM) of freshly prepared NaBH4 solution was added to the precursor mixture and the reaction was continued for 2 h to obtain Ag(NH4)2 +Reduced to silver nanoparticles.

[0045] (2) Then, 0.01 M HCl was added to the reaction mixture to adjust the pH to about 7.0, and stirring was continued at room temperature for 4 h to decompose the excess NaBH4; then, 1.5 mg (0.003 mmol) of chloroplatinic acid hexahydrate was added and stirred overnight, and finally, 1.5 mL (6.7 mM) of freshly prepared NaBH4 solution was added and reacted for 2 h to stop the reaction; 0.01 M HCl was added again to adjust the pH to about 7.0.

[0046] (3) The reaction solution was centrifuged three times with acetone and purified water at 8000 r / min, and dried under vacuum at 50 °C to finally obtain FA@Ag-Pt QDs.

[0047] Example 2

[0048] On the basis of Example 1, the feed ratio of Ag element to Pt element and the feed ratio of folic acid to Ag and Pt were changed respectively to prepare the target product FA@Ag-Pt QDs nano-mimetic enzyme.

[0049] Table 1 Ag and Pt feed molar ratio is variable

[0050]

[0051] Table 2 The molar ratio of folic acid to Ag and Pt is variable

[0052]

[0053]

[0054] The UV-visible spectra of the FA@Ag-Pt QDs-TMB-H2O2 system obtained under each variable were tested for absorbance intensity at 652nm, and the results were as follows: Figure 1 As shown in ab.

[0055] Performance characterization and testing:

[0056] 1. The structure of the FA@Ag-Pt QDs nano-mimetic enzyme prepared in Example 1 was characterized by TEM, DLS, EDS, XRD, FTIR, zeta potential and XPS. Figure 2 and 3 shown. Figure 2 The TEM of a confirmed that the morphology of FA@Ag-Pt QDs material is spherical particles of about 4nm, which indicates that folic acid and silver platinum nanoparticles are successfully compounded together. Figure 2 DLS of b further shows that the quantum dot material presents a normal distribution trend. Figure 2The EDS of c proves that C, N, O, Ag, and Pt elements exist in FA@Ag-PtQDs, and the molar ratio of Ag to Pt is 7:3, which is completely consistent with the feed dosage ratio; Figure 2 d It can be seen that the material itself has good fluorescence spectrum performance (the excitation peak and emission peak are 267nm and 455nm, respectively), which further confirms the nanosize of quantum dots; the EDS illustration is the HR-TEM of the material. FA@Ag-Pt QDs have two crystal plane spacings of 0.212nm and 0.238nm, which correspond to the (111) crystal plane of silver nanoparticles and the (111) crystal plane of platinum nanoparticles, respectively. The crystal plane spacing of silver nanoparticles is not very clear, while that of platinum nanoparticles is relatively clear, which indicates that the synthesized FA@Ag-Pt QDs material may be a silver-platinum core-shell structure.

[0057] The XRD of the composite material clarifies the crystal phase and crystallinity of FA@Ag-Pt QDs material, which has four characteristic peaks, such as Figure 2 As shown in Figure d, 2θ is 38.99°, 64.82°, 66.21° and 77.65°, respectively. The weak peak near 2θ=64.82° is consistent with the (220) crystal plane of Ag, while the strong peak near 2θ=38.99° and the weak peaks near 66.21° and 77.65° are attributed to the (111), (220) and (311) crystal planes of PtNPs. The diffraction peak signal of Ag in FA@Ag-Pt QDs is not very strong, indicating that most of the Ag in the material is wrapped by Pt. In addition, the Pt peak is negatively shifted compared with the literature, and the expansion of the Pt lattice to Ag also indicates the formation of the AgPt core-shell structure. Figure 3 The FA and FA@Ag-Pt QDs FT-IR spectra of b show that the FA spectra at 3537 and 3467 cm -1 The FT-IR peaks at 1694, 1613, 1484 and 1411 cm-1 are attributed to the stretching vibrations of NH and NH2 in NH. -1 The FT-IR peaks correspond to the stretching vibrations of C=O and aromatic rings. In the spectrum of FA@Ag-Pt QDs, the peak at 1694 cm -1 The characteristic peak intensity of the C=O bond at the composite material is significantly reduced to a weak shoulder peak, and the disappearance of the C=O stretching vibration peak and the weakening of the C=O bond indicate that the active N and O with lone electron pairs in FA are coordinated with the vacant d orbitals in the AgPt quantum dots. In addition, due to the strong interaction between AgPt NPs and nitrogen-containing aromatic heterocycles, the stretching vibration peaks on the aromatic rings of the composite material are shifted to 1607, 1511, and 1386 cm -1 , offset by 5, -27 and 25cm respectively -1, which further illustrates this point. There is a strong electrostatic interaction between FA and Ag-Pt quantum dots, which makes FA tightly adsorbed on the surface of Ag-Pt quantum dots.

[0058] For the zeta potential of the components of FA@Ag-Pt QDs materials in aqueous solution, the zeta potential of the silver-platinum nanomaterial alone is 5.6 mV, while the zeta potential of the FA@Ag-Pt QDs material after being composited with folic acid is -32.3 mV, see Figure 3 c. Its absolute value is significantly higher than that of the single silver-platinum nanomaterial, which indicates that the silver-platinum nanomaterial is successfully constructed with folic acid and the stability of the material after folic acid modification is greatly improved. The elemental composition and valence of FA@Ag-Pt QDs material were investigated by XPS. Figure 3 d X-ray photoelectron wide-angle spectrum confirmed that the prepared FA@Ag-Pt QDs material contained all the feed elements Ag, Pt, C, N and O. Figure 3 The characteristic peaks at 373.69 eV and 367.69 eV in the Ag 3d high-resolution XPS spectrum of e correspond to Ag 0 3D 3 / 2 and 3D 5 / 2 track, which indicates that the Ag + Has been completely reduced to Ag 0 . Figure 3 In the high-resolution XPS spectrum of Pt 3d, 75.20 eV and 71.90 eV are respectively attributed to Pt 2+ 4f 5 / 2 and 4f 7 / 2 orbital, while 73.90 eV and 70.56 eV are attributed to Pt 0 4f 5 / 2 and 4f 7 / 2 orbit, and Pt 2+ With Pt 0 The integral area ratio is about 0.95, indicating that the Pt 4+ Not completely reduced to Pt 0 , but Pt 2+ With Pt 0 coexistence, which will enhance the peroxidase-mimetic activity of FA@Ag-Pt QDs nanozymes.

[0059] 2. The detection ability test of the FA@Ag-Pt QDs nano-mimetic enzyme prepared in Example 1 includes the following steps:

[0060] (1) Preparation of FA@Ag-Pt QDs standard solution: The prepared FA@Ag-Pt QDs material was ultrasonically dispersed in double distilled water to prepare a FA@Ag-Pt QDs standard solution with a concentration of 0.02 mg / mL, which was stored at room temperature for later use.

[0061] (2) Hg 2+ ,I - Preparation of TMB and H2O2 standard solutions

[0062] Weigh 1.53 g (0.1 mmol) of mercuric nitrate, 1.66 g (0.1 mmol) of potassium iodide, and 0.36 g (1.5 mmol) of TMB (3,3',5,5'-tetramethylbenzidine) and dissolve them in 1000.0 mL of double distilled water and 1000 mL of DMSO, respectively. Measure 100.0 mL of 30% (10 mol) H2O2 and dilute it to 1000.0 mL with double distilled water to prepare 10.0 mM Hg 2+ , 10.0 mM I - , 1.5 mM TMB and 3% (1 M) H2O2 standard solution, stored at room temperature and diluted to the required concentration when used.

[0063] (3) Preparation of actual sample solution:

[0064] (i)Hg 2+ The samples for testing were prepared as follows:

[0065] 100.0 mL of tap water and surface water samples were randomly measured, filtered three times with a microporous filter membrane with a pore size of 0.22 μm, and stored at room temperature for later use.

[0066] Sprite and sparkling water samples were purchased randomly, filtered three times with a microporous filter membrane with a pore size of 0.22 μm, and stored at room temperature for later use.

[0067] (ii)I - The samples for testing were prepared as follows:

[0068] Iodine tincture was produced by Qingdao Haishi Hainuo Yingnuowei Disinfection Technology Co., Ltd. Iodine salt was prepared by dissolving 3.33 mg of solid in 5 mL of pure water and storing it at room temperature for later use.

[0069] Randomly weigh 0.5 g of rinsed kelp and laver, add 25 mL of triple distilled water, squeeze the juice with a commercial juicer, collect the supernatant, centrifuge at 9000 r / min for 20 min to obtain the corresponding samples, and store them at room temperature for later use.

[0070] (4) In order to make the experimental results more reasonable, before studying the catalytic activity of FA@Ag-Pt QDs simulating peroxidase, the temperature (20-60 °C), reaction time (0-30 min), pH (2.5-7.0), c TMB (0.025~0.15mM) and c H2O2 (0.0167~0.1333M) and other conditions were optimized, and the results were as follows Figure 4 The results show that the best experimental conditions for FA@Ag-Pt QDs enzyme mimicking are 0.1mM TMB, 0.1M H2O2, pH 4.0, and incubation at 25℃ for 15min.

[0071] (5) FA@Ag-Pt QDs simulated peroxidase catalytic activity test: 240 μL of the FA@Ag-Pt QDs material in (1), 200 μL of pH 4.0 citric acid-phosphate buffer solution, 200 μL of TMB in (2) and 300 μL of H2O2 in (2) were added to a 5 mL centrifuge tube, and the volume was adjusted to 3 mL with pure water. The mixture was mixed evenly and aged at room temperature for 15 min. The UV-visible spectrum of the mixture was measured at 300-800 nm and the color change was observed. The results are as follows: Figure 5 The results show that FA@Ag-Pt QDs nanomimetic enzyme can catalyze the oxidation of TMB in the presence of H2O2, and produce an obvious UV-visible characteristic absorption peak at 652nm, accompanied by a significant change in color from colorless to blue. The presence of TMB alone does not cause FA@Ag-Pt QDs nanomimetic enzyme to undergo UV-visible absorption and color change.

[0072] The FA@Ag-Pt QDs nanomimetic enzyme prepared in Example 1 was used to investigate its catalytic oxidation mechanism of TMB. Figure 5 c. Use hydroxylamine hydrochloride to determine whether O2 is produced during the reaction ·- , the common ·OH scavenger isopropanol was used to determine whether ·OH free radicals were generated during the reaction. From the UV-visible spectrum, it was observed that the UV absorption peak at 652nm was close to zero after the addition of isopropanol, accompanied by a color change from blue to colorless, indicating that ·OH free radicals were generated during the catalytic oxidation of TMB by FA@Ag-Pt QDs, which accelerated the oxidation of TMB. At the same time, there was no obvious change in the absorption intensity and color after the addition of hydroxylamine hydrochloride, which indicated that there was no O2 ·- During the process of FA@AgNPs accelerating TMB oxidation, no O2 was generated. ·- In addition, the method of filling the reaction system with nitrogen also indirectly verified that no O2 was produced during the catalytic oxidation of TMB by FA@Ag-Pt QDs. ·- ( Figure 5 d), thus, it was demonstrated that the enzyme mimicking mechanism of FA@Ag-Pt QDs is peroxidase mimicking.

[0073] (6) FA@Ag-Pt QDs simulated peroxidase catalytic activity test: 240 μL of the FA@Ag-Pt QDs material in (1), 200 μL of pH 4.0 citric acid-phosphate buffer solution, 200 μL of TMB in (2) and 300 μL of H2O2 in (2) were added to a 5 mL centrifuge tube, and the volume was adjusted to 3 mL with pure water. The mixture was mixed evenly and aged at room temperature for 15 min. The UV-visible spectrum of the mixture was measured at 300-800 nm and the color change was observed. The results are as follows: Figure 6 The results show that FA@Ag-Pt QDs nanomimetic enzyme can catalyze the oxidation of TMB in the presence of H2O2, and produce an obvious UV-visible characteristic absorption peak at 652nm, accompanied by a significant change in color from colorless to blue. The presence of TMB alone does not cause FA@Ag-Pt QDs nanomimetic enzyme to undergo UV-visible absorption and color change.

[0074] (7) Investigation of kinetic parameters of FA@Ag-Pt QDs enzyme mimics: We conducted a kinetic experiment of hydrogen peroxide mimics enzyme under the optimal experimental conditions (240 μL 0.02 mg / mL FA@AgPt QDs, pH 4.0, 200 μL 1.5 mM TMB, 300 μL 1.0 M H2O2, incubation at room temperature for 15 min). The results are as follows: Figure 6 As shown. The concentrations of TMB (0.03-0.10 mmol / L) and H2O2 (0.03-0.10 mol / L) were changed respectively, and the absorption intensity of the ultraviolet absorption peak at 652 nm within 600.0 s was recorded. According to the Michaelis-Menten equation, the corresponding initial reaction rate v was calculated, and the relationship between the reaction rate and the TMB concentration and the H2O2 concentration was plotted (v-cTMB and vc H2O2 ) and the double reciprocal curve of the reaction rate inversely and the TMB concentration and the H2O2 concentration inversely according to the Lineweaver-Burk equation ((1 / v)-(1 / c TMB ) and (1 / v)-(1 / c H2O2 )), and then the Michaelis constant (K m ) and the maximum reaction rate (V max ) are 0.01mM / 2.95×10 - 8 M.s -1 and 1.15mM / 3.88×10 -8 M.s-1 . By attaching Figure 6 The three curves c and 6d are basically parallel to each other, proving that FA@Ag-Pt QDs enzyme mimics follow the classic ping-pong mechanism.

[0075] (8) Catalytic colorimetric detection of Hg 2+ and I - Selectivity: 240 μL of FA@Ag-Pt QDs material from (1), 200 μL of pH 4.0 citric acid-phosphate buffer solution, 200 μL of TMB from (2), 300 μL of H2O2 from (2), and 200 μL of Hg 2+ and I - , standard solutions of interfering ions (common metal ions, anions and organic standard aqueous solutions) or mixed solutions (standard solutions of interfering ions and Hg 2+ or I - Mixed solution of standard solution) or sample solution to be tested (actual sample solution such as water sample, beverage, etc.), dilute to 3mL with pure water, mix evenly and age at room temperature for 15min, measure its UV-visible spectrum at 300-800nm ​​and observe its color change. The result is as follows Figure 7 As shown in a, all metal ions (Fe 2+ 、Bi 3+ , Pb 2+ , K + 、Ni 2+ 、Cd 2+ 、Co 2+ , Fe 3+ Mg 2+ Cr 3+ , Ba 2+ 、Zn 2+ , Cu 2+ 、Ag + , Hg 2+ ) exists, only Hg 2+ When it exists, the UV-visible spectrum of FA@Ag-Pt QDs-TMB-H2O2 system at 652nm is quenched, and the color (inset) fades from blue to colorless, indicating that FA@Ag-Pt QDs-TMB-H2O2 system is sensitive to Hg 2+ There is a special subtractive color response; from the attached Figure 7 b and 7c, it can be seen that common anions (I – Br - 、S2O4 2- 、S2O3 2- 、S2 - 、F - 、NO2 - 、SO4 2- ,Ac- , Cl - 、SO3 2- 、NO3 - 、CO3 2- 、C2O4 2- PO4 3- and CN - ) and organic substances (uric acid, ascorbic acid, urea, glucose, phenylalanine, glycine and bovine serum albumin), only I – The UV-visible spectrum of the FA@Ag-Pt QDs-TMB-H2O2 system at 652 nm was significantly enhanced, and the color of the solution changed from light blue to blue, indicating that the FA@Ag-Pt QDs-TMB-H2O2 system has a strong affinity for I - There is a special hyperchromic response. That is, the FA@Ag-Pt QDs-TMB-H2O2 system has a special hyperchromic response to Hg 2+ and I – It has good naked eye colorimetry and spectral response, and has no obvious interference from common metal ions, anions and organic matter.

[0076] On this basis, we further 2+ Selectivity experiments were conducted under the condition of coexistence with other metal interferences. The intensity change of the UV absorption peak at 652nm is as follows Figure 7 d, the results show that when Hg 2+ When coexisting with other metal interfering substances, the UV absorption peak intensity changes very little, within 5% error, which indicates that other interfering substances have a significant effect on Hg 2+ There is basically no effect on the detection. - Selectivity experiments were carried out under the condition of coexistence with other anions and organic interferences. The intensity of the UV absorption peak at 652nm changed as shown in Figure 7 e and 7f, the UV absorption peak intensity is also within 5% error, indicating that the FA@AgPt QDs-TMB-H2O2 system has a good effect on I - The selectivity of Hg 2+ and I - They cannot coexist at the same time and will not interfere with each other. The FA@AgPt QDs-TMB-H2O2 system can be used for colorimetric amplification signal detection of Hg 2+ and I - .

[0077] (9) FA@AgPt QDs catalytic colorimetric detection of Hg 2+ and I - Quantitative parameters: In order to determine the colorimetric detection of Hg by FA@AgPt QDs 2+ and I -The quantitative analysis parameters (i.e., the linear range, linear relationship equation, and detection limit of the analysis) are used for the subsequent quantitative detection of Hg 2+ and I - The practical application of different concentrations of Hg 2+ or I – UV-visible spectroscopic titration experiment and color change comparison experiment. Figure 8 As shown in a, with the increase of Hg 2+ The absorption intensity of the FA@AgPt QDs-TMB-H2O2 system at 652 nm gradually decreases with the gradual increase in concentration, accompanied by a color change from blue to colorless (inset). 2+ The concentration is 1×10 -9 to 116.67×10 -9 M and 116.67×10 -9 to 1666.67×10 -9 Within the range of M, ΔA 652 (A0-A 652 ) and c Hg 2+ There are two good linear relationships between them, and the linear equations are ΔA 652 =0.0015c Hg 2+ +0.0055, R 2 =0.984 and ΔA 652 =0.0018c Hg 2+ +0.17, R 2 =0.992, see Figure 8 b. Also with I - As the concentration increases, the absorption intensity of the FA@AgPt QDs-TMB-H2O2 system at 652 nm continues to increase, and the blue color gradually deepens (inset). Figure 8 c.I - The concentration is 1×10 -7 to 13.33×10 -7 M and 13.33×10 -7 M to 100.00×10 -7 Within the range of M, ΔA 652 With c I - There are two good linear relationships between them, and the linear equations are ΔA 652 =0.0081c I - +0.0034, R 2 = 0.990 and ΔA 652 =0.0015c I -+0.087, R 2 =0.998, see Figure 8 d. From Figure 8 b and 8d we can further deduce: Colorimetric detection of Hg 2+ and I - The detection limits were 4.00×10 -10 and 6.56×10 -8 FA@AgPt QDs is an excellent quantitative detection method for Hg 2+ and I - Catalytic colorimetric sensor.

[0078] (10) Hg in the sample 2+ and I - Practical application of visual detection: quantitative analysis of Hg based on (9) 2+ and I - The Hg content in each sample solution prepared in (3) was detected according to the law. 2+ and I - : Add 240 μL of the FA@Ag-Pt QDs material in (1), 200 μL of pH 4.0 citric acid-phosphate buffer solution, 200 μL of TMB in (2), 300 μL of H2O2 in (2), 200 μL of the sample solution to be tested, or the sample solution to be tested to a 5 mL centrifuge tube, dilute to 3 mL with purified water, mix well and age at room temperature for 15 min, measure its UV-visible spectrum at 300-800 nm and observe its color change, and according to the measured A 652 , ΔA is calculated 652 After the value is obtained, the corresponding linear regression equation is ΔA 652 =0.0015c Hg 2+ +0.0055, ΔA 652 =0.0018c Hg 2+ +0.17 or ΔA 652 =0.0081c I - +0.0034, ΔA 652 =0.0015c I - +0.087, and finally calculated the Hg in the sample 2+ and I - The concentrations are shown in Tables 3 and 4.

[0079] Table 3 Visual colorimetric detection results of FA@Ag-Pt QDs-TMB-H2O2-Hg system (n=5) a

[0080]

[0081] a c FA@AgPt QDs =0.02 mg / mL, pH 4.0;

[0082] Table 4 Visual colorimetric detection results of FA@Ag-Pt QDs-TMB-H2O2-I system (n=5) a

[0083]

[0084] a c FA@AgPt QDs =0.02 mg / mL, pH 4.0;

[0085] b The actual value is the value in the table × 30, because the sample was diluted 30 times before testing.

[0086] Based on the above quantitative detection conclusions, FA@AgPt QDs peroxidase mimics were applied to the detection of actual samples, such as Hg 2+ Applied to actual water samples and some beverage samples, I - It is used in some iodine-rich samples such as seafood, iodized salt and iodine tincture, see Table 1 and Table 2. The standard spike method is used to determine Hg 2+ and I - The standard deviation (RSD) and recovery (%) of Hg in the actual sample are shown in Table 1. 2+ The colorimetric detection standard deviation RSD was less than 2.5%, and the recovery rate was between 96.8% and 104.3%. - The colorimetric detection standard deviation RSD was less than 4.9%, and the recovery rate was between 93.9% and 105.3%. This shows that the above-mentioned FA@AgPt QDs peroxidase mimetic enzyme can be used for the detection of Hg in actual samples. 2+ and I - The visible colorimetric detection has the characteristics of high sensitivity and accurate detection results.

[0087] The above description only illustrates several embodiments of the present invention, and it cannot be understood as limiting the scope of the present invention. It should be pointed out that other persons in the art may make modifications, substitutions, improvements, etc. without departing from the concept and scope of the present invention, and these all belong to the protection scope of the present invention. Therefore, the scope of the present invention shall be based on the described claims.

Claims

1. A folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme FA@Ag-Pt QDs, characterized in that: Through the electrostatic interaction between metal Ag and Pt cations and the negative charge or lone pair electrons on folate, Ag and Pt cations are adsorbed onto the surface of folic acid, and then through a reduction reaction, folic acid-stabilized silver-platinum nano-quantum dot particles are obtained, and the size of the material is at the nanometer level.

2. The nanozyme according to claim 1, characterized in that In the FA@Ag-Pt QDs nanozyme, the molar ratio of Ag element to Pt element is 9:1~5:

5.

3. A method for preparing a folic acid-stabilized silver-platinum bimetallic quantum dot-based nanozyme, characterized in that: The steps include: (1) mixing ammonium folic acid salt, silver ammonium ions and a polyhydroxy alcohol compound to obtain a precursor mixture, stirring the precursor mixture to react; and then adding a reducing agent to reduce the mixture to obtain silver nanoparticles; (2) then adding HCl to the reaction mixture to adjust the pH, stirring, adding chloroplatinic acid hexahydrate, adding a reducing agent for reduction, and adding HCl again to adjust the pH; (3) The reaction solution was washed by centrifugation with acetone and purified water and dried under vacuum to finally obtain the desired folic acid-stabilized silver-platinum bimetallic nano-quantum dot nanozyme FA@Ag-Pt QDs.

4. The preparation method according to claim 3, characterized in that: In the FA@Ag-Pt QDs nanozyme, the molar ratio of Ag element to Pt element is 9:1-5:5; the ratio of folic acid to the sum of the molar ratios of Ag and Pt is 0.1:1-10:

1.

5. The preparation method according to claim 3, characterized in that In step (1), the feed ratio of the ammonium folic acid salt to the silver ammonium ion, the polyhydroxy alcohol compound and the reducing agent is 4.42-44.2 mg: 1.54-0.86 mg: 16 mL: 0.38 mg.

6. The preparation method according to claim 3, characterized in that: In step (1), the polyhydric alcohol compound is at least one of ethylene glycol, glycerol, and polyvinyl alcohol.

7. The preparation method according to claim 3, characterized in that: In steps (1) and (2), the reducing agent is at least one of vitamin C, hydrazine hydrate, glucose, and sodium borohydride.

8. The preparation method according to claim 3, characterized in that The feed ratio of the chloroplatinic acid hexahydrate and the reducing agent described in step (2) to the ammonium folic acid salt described in step (1) is 0.17-0.86 mg: 0.32-0.44 mg: 4.42-44.2 mg.

9. The preparation method according to claim 3, characterized in that: The pH values ​​described in step (2) are all between 5.0 and 8.

0.

10. Application of the nanozyme according to claims 1-2 or the FA@Ag-Pt QDs nanozyme prepared by any method according to claims 3-9 in the fields of environmental water, food, medicine, etc., characterized in that: The application is to use the FA@Ag-Pt QDs nanozyme to carry out Hg 2+ or I – The detection includes the following steps: S1. Add the colorimetric substrate 3,3',5,5'-tetramethylbenzidine (TMB), hydrogen peroxide (H2O2), disodium hydrogen phosphate-citric acid buffer solution, and the sample solution to be tested to the FA@Ag-Pt QDs standard solution to obtain the test solution; S2. Observe the color change of the test liquid.